1887 Terr. of Mont. Laws 68 - (:unkn) unknown (My University, 1887)
Extraordinary Session, An Act to Amend an Act Entitled An Act Concerning the Storage of Gunpowder, § 2: No person, company, or corporation shall store, deposit or keep within the limits of any city, town or village, gunpowder, nitroglycerine, guncotton, dynamite, and other dangerous or powerful explosives exceeding fifty pounds, and no magazine or storehouse where such explosives are stored or kept, shall hereafter be located nearer than one-half mile from such city, town or village
Keywords: GUNPOWDER - STORAGE